Políticas curriculares e inclusão digital: uma proposta de trilhas formativas para docentes - Vargas, Fernanda Dorneles (2024)
This research project is linked to the Professional Master's Course, the Postgraduate Program in Public Policies and Educational Management and the Study Group on Education, Technologies and Society - INTERFACES/CNPq. Addresses the topic of Digital Inclusion, considering curricular policies in Basic Education. Its general objective is to understand how the Escola Municipal de Ensino Fundamental Pinheiro Machado is mobilizing in relation to digital inclusion, taking into account existing public educational policies, with emphasis on the Common National Curricular Base (BNCC) and those that guide education in the municipality of Santa Maria. It consists of qualitative research, of the Case Study type, to be carried out at the school, with teachers and school management. To construct the data, it was decided to use documentary research and the application of a questionnaire and interview. Their assessment will be made through documentary analysis of the public policies covered in this research and discursive textual analysis of the questionnaires and interviews. The theoretical framework is organized based on authors Imbernón(2010), Lemos(2007) and Pischetola(2016). The ideal product is Training Trails for teachers to promote digital inclusion. The contributions from the trails will provide opportunities for the qualification of the teaching team, in order to expand their knowledge in educational practices. It is hoped that with this research the school's teaching staff will be able to give new meaning to their pedagogical practices by implementing digital inclusion in their training process.